Development of InShot-Based Interactive Learning Videos for Probability Learning in Grade VIII Students - Nurul Latifah; Indah Widyaningrum; Reza lestari (MASI Mandiri Edukasi, 2026)
Probability learning is often considered difficult because students struggle in understand abstract concepts and relate them to real-life situations. In addition, the integration of contextual, interactive multimedia aligned with local tourism contexts in mathematics learning remains limited, even though such approaches can support more meaningful, student-centered learning experiences. This study aimed to develop and evaluate an InShot-assisted interactive learning video integrated into the tourism context of Pagaralam City to support probability learning among junior high school students. This research employed a Research and Development (R&D) approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, expert validation questionnaires, and teacher and student response questionnaires conducted during one-to-one, small-group, and field trials. The results showed that the developed media achieved high feasibility and practicality in supporting probability learning. The integration of contextual tourism content, interactive video features, and mobile-based learning media created more engaging, meaningful, and interactive learning experiences for students. The developed media also supported students’ participation and conceptual understanding through contextual and visual learning activities. Therefore, this study contributes to contextual mathematics education by integrating local cultural potential with interactive multimedia learning in probability instruction.